Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

hi i have a problem for this Differential Equations : $$ \frac{d^{3}y}{dx^3} - 9\frac{dy}{dx} = 10 - 4x $$ i know first we must solve the homogeneous equation: and my result is : $C_1 + C_2e^{3x} + C_3e^{-3x}$

i'm really confused to find yp from $10 - 4x$, my friend said it must : $(ax+b)x$ my question is :
1. why it's not $c - (ax + b)$,
2. if it same with $c1$ from yh(homogeneous solution ) why we not multiply $c$ with x? so $yp = cx - (ax + b) $
3. and why $(ax+b)$ must be multiplied with $x$??

can someone explain me? thanks for anyone helped me.

share|cite|improve this question
If you want to know why you can't use $y_p=c-(ax+b)$ or $y_p=cx-(ax+b)$ then you should try to use one of those, and see what happens. When you see why it doesn't work, you will understand why it is necessary to try $y_p=(ax+b)x$. – Gerry Myerson Jan 28 '13 at 11:43

It is straightforward to see that if a polynomial solves the inhomogeneous ODE $$\tag{ODE} y'''-9y'=10-4x, $$ it must be of degree $2$. Hence, we have $$ p'''(x)-9p'(x)=10-4x \iff -9p'(x)=10-4x \iff p'(x)=-\frac{10}{9}+\frac49x, $$ i.e. $$ p(x)=-\frac{10}{9}x+\frac29x^2 $$ Setting $$\tag{2} z=y-p,\ u=z' $$ we see that $z$ solves the homogeneous equation $$\tag{ODE'} z'''-9z'=0, $$ and therefore $u$ solves the 2nd order ODE $$ u''-9u=0 $$ whose solution is given by $$ u(x)=-3c_1e^{-3x}+3c_2e^{3x}, \ c_1,c_2 \in \mathbb{R}. $$ It follows that $$ z(x)=c_3+c_1e^{-3x}+c_2e^{3x},\ c_3 \in \mathbb{R} $$ and $$ y(x)=c_3-\frac{10}{9}x+\frac29x^2+c_1e^{-3x}+c_2e^{3x}. $$

share|cite|improve this answer

Related problems: (I). We use the annihilator method. Let $D=\frac{d}{dx}$. Now, apply $D$ twice to both sides of the differential equation to transform it to a homogeneous differential equation, so we have

$$ D^2(D^3-9D)y=D^2(10-4x)=0\implies D^3(D^2-9)y=0. $$

The last equation gives you the auxiliary equation of the new homogeneous differential equation which allow us to write the general solution of the new homogeneous differential equation

$$ m^3(m^2-9)=0 \implies m=0,0,0,3,-3,$$

which gives the general solution

$$ y(x) = c_1+c_2x+c_3x^3+c_4e^{3x}+c_5e^{-3x}=(c_1+c_4e^{3x}+c_5e^{-3x})+c_2x+c_3x^2 \rightarrow(1).$$

You can recognize that the expression between the brackets in equation $(1)$ corresponds to the solution of the original homogeneous differential equation

$$ \frac{d^{3}y}{dx^3} - 9\frac{dy}{dx} = 0. $$

So, the other terms in $(1)$ tell you about the form of $y_p$ of the original differential equation which you assume as

$$ y_p=Ax +Bx^2. $$

share|cite|improve this answer

Inhomogeneous solution here will be of the form

$$y_p(x) = a (10-4 x)^2 + b$$

such that $y_p(0) = 0$ (subsequent values of $y_p'(0)$ and $y_p''(0)$ will have to be taken into account into overall initial conditions on solution $y$). The reason it takes a quadratic form is that you have a $y'$ but no $y$ in your equation.

Putting this form into the equation and solving for $a$ and $b$ (from the initial condition), I get

$$y_p(x) = \frac{1}{72} (10-4 x)^2 - \frac{25}{18}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.